Pressing ethical issues in considering pediatric deep brain stimulation for obsessive-compulsive disorder - Katrina A. Muñoz (Elsevier, 2021)
Background: Refractory obsessive-compulsive disorder (OCD) among adults is the first psychiatric indication of deep brain stimulation (DBS) to receive an FDA Humanitarian Device Exemption (HDE). Given the HDE approval and encouraging evidence that has since emerged, exploration of DBS for OCD may expand to adolescents in the future. More than 100,000 adolescents in the U.S. suffer from refractory OCD, and there is already a precedent for the transition of DBS in adults to children in the case of dystonia. However, the risk-benefit analysis of pediatric DBS for OCD may be more complex and raise different ethical questions compared to pediatric DBS for dystonia. Objective: This study aimed to gain insight into pressing ethical issues related to using DBS in adolescents with OCD. Methods: Semi-structured interviews were conducted with clinicians (n = 25) caring for pediatric patients with refractory OCD. Interview transcripts were coded with MAXQDA 2018 software and analyzed using thematic content analysis to identify emergent themes. Results: Five central themes were identified in clinician responses, three of which were exacerbated in the pediatric DBS setting. Clinicians expressed concerns related to conditions of decision-making including adolescents' capacity to assent (80%), the lack of evidence about the outcomes and potential unknown effects of using DBS in adolescents with OCD (68%), and the importance of exhausting other treatment options before considering DBS (20%). Conclusions: Strategies to address clinician concerns include implementation of validated decision support tools and further research into the outcomes of pediatric DBS for OCD to establish clear guidelines for patient selection.